Lie algebras, lie superalgebras, vertex algebras and related topics - 2012-2014 Southeastern Lie Theory Workshop Series; Misra, Kailash C.; Nakano, Daniel K.; Parshall, Brian J.; Categorification of Quantum Groups and Representation Theory (North Carolina State University 21-22 Apr, 2012); Lie Algebras, Vertex Algebras, Integrable Systems and Applications (College of Charleston 16-18 Dec, 2012); Noncommutative Algebraic Geometry and Representation Theory (Louisiana State University 10-12 May, 2013); Representation Theory of Lie Algebras and Lie Superalgebras (University of Georgia 16-17 May, 2014) (Providence : American Mathematical Society, 2016)
This book contains the proceedings of the 2012-2014 Southeastern Lie Theory Workshop Series held at North Carolina State University in April 2012, at College of Charleston in December 2012, at Louisiana State University in May 2013, and at University of Georgia in May 2014. Some of the articles by experts in the field survey recent developments while others include new results in representations of Lie algebras, and quantum groups, vertex (operator) algebras and Lie superalgebras.
Includes bibliographical references.
Keywords: Lie algebras -- Congresses; Lie superalgebras -- Congresses; Vertex operator algebras -- Congresses